Acute toxicity, brine shrimp cytotoxicity and relaxant activity of fruits of callistemon citrinus curtis - Shah Ismail; Ali Shah Syed; Ahmed Ghayour; Ali Niaz; Ghias Mehreen; Khan Imran (BMC Complementary and Alternative Medicine, 2011)
Abstract Background Callistemon citrinus Curtis belongs to family Myrtaceae that has a great medicinal importance. In our previous work, fruits of Callistemon citrinus were reported to have relaxant (antispasmodic) activity. The current work describes the screening of fractions of the crude methanol extract for tracing spasmolytic constituents so that it shall help us for isolation of bioactive compounds. Acute toxicity and brine shrimp cytotoxicity of crude methanol extract are also performed to standardize it. Methods The crude methanol extract was obtained by maceration with distilled water (500 ml) three times and fractionated successively with n-hexane, chloroform, ethyl acetate and n-butanol (300 ml of each solvent). Phytochemical analysis for crude methanol extract was performed. Acute toxicity studies were performed in mice. Brine shrimp cytotoxicity studies were performed to determine its cytotoxicity and standardize it. In other series of experiments, rabbits' jejunum preparations were used in screening for possible relaxant activities of various fractions. They were applied in concentrations of 0.01, 0.03, 0.1, 0.3, 1.0, 3.0, 5.0 and 10.0 mg/ml on spontaneous rabbits' jejunum preparations. In similar fashion, fractions were also tested on KCl (80 mM) -induced contractions. Calcium chloride curves were constructed in K-rich Tyrode's solution. The effects of various fractions were tested on calcium chloride curves at concentrations 1.0, 3.0, 5.0 and 10.0 mg/ml. Curves of verapamil used as reference drug at concentration 0.1 μM and 0.3 μM were also constructed. The curves were compared with their respective controls for possible right shift. Results Methanol extract tested strongly positive for saponins and tannins. However, it tested mild positive for presence of proteins, amino acids, carbohydrates and phenolic compounds. LD50 value for crude methanol extract is 476.25 ± 10.3 (470-481, n = 4) mg/ml. Similarly, EC50 value for brine shrimp cytotoxicity is 65.5 ± 7.28 (60.8- 69.4, n = 4) mg/ml. All the fractions relaxed the spontaneous and KCl-induced contractions. EC50 values (mg/ml) for effects of ethyl acetate fraction on spontaneous and KCl induced contractions are 2.62 ± 0.78 (2.15-3.0, n = 4) and 3.72 ± 0.86 (3.38-4.28, n = 4) respectively. Respective EC50 values (mg/ml) for n-butanol fraction are 3.59 ± 0.2(3.07-3.9, n = 4) for spontaneous, and 5.57 ± 0.2 (5.07-6.11, n = 4) for KCl- induced contractions. EC50 value for control calcium chloride curve (without extract) is -2.73 ± 0.19 (-2.6 - -2.81, n = 4) while EC50 for curves treated with 5.0 mg/ml of chloroform is -2.22 ± 0.02 (-2.16 - -2.3, n = 4). EC50 value for ethyl acetate treated (1.0 mg/ml) tissues is -1.95 ± 0.10 (-1.88 - -2.0, n = 4) vs. control EC50 = -2.71 ± 0.08 (-2.66 - -2.76, n = 4). All the fractions, except n-hexane, showed a right shift like that of verapamil (EC50 = -1.72 ± 0.15 (-1.62 - -1.8, n = 4) vs. Control EC50 = -2.41 ± 0.06 (-2.38 - - 2.44, n = 4), a standard drug that blocks voltage operated calcium channels. Conclusion Relaxant constituents were more concentrated in ethylacetate fraction followed by chloroform, n -butanol and aqueous fractions that warrant for its isolation. The crude methanol extract is safe at concentration 250 mg/ml or below and results of brine shrimp cytotoxicity assay imply the plant specie may be a source of cytotoxic agents.